Relationship between Kinesiophobia, Foot Pain and Foot Function, and Disease Activity in Patients with Rheumatoid Arthritis - Ramos Petersen, Laura; Lópezosa-Reca, Eva (My University, 2023)
Physical activity should be promoted in all people with RA, even in challenging times, such as a pandemic, to improve disease outcomes, well-being, and mental health, despite functional disability. The level of pain is related to the level of kinesiophobia in patients with RA.
Keywords: Artritis reumatoide; Rheumatoid Arthritis; Kinesiophobia; Foot pain